OsTKPR2 is part of a sporopollenin-producing metabolon required for exine formation in rice - Yang, Huiting (Journal of experimental botany, 2023)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.